Meneropong Arus Pendidikan Multikultural di Indonesia - Purwanti, Erik; Erlangga, Adam Baustin; Agustian, Niar; Afadh, Muhamad (ARZUSIN, 2022)
Indonesia is a country that has pluralistic diversity. These varieties can be viewed from two perspectives, namely a horizontal perspective and a vertical perspective. The horizontal perspective covers the diversity of religion, ethnicity, regional language, clothing, food, and culture. The vertical perspective includes differences in education level, economy, place of residence, occupation and socio-cultural diversity. The diversity of our nation makes us pay attention to the importance of multicultural education in anticipation of negative social phenomena that may come from diversity, race, ethnicity, religion, and the diversity of values that exist in society. Multicultural education can be implemented through a learning model substantially by acknowledging and respecting cultural diversity.